Incorporation of legal entities in Brazil and their use in the business models of startups (Research, Society and Development, 2021)
The present study envisions a few notes about the possible business models in Brazilian legislation and startups. In this perspective, this article, through exploratory research, of a qualitative nature, deductive method, collection of documentary and bibliographic data, proceeded in order to carry out a thorough analysis of the normative framework that deals with startups. In addition, the extreme extraction of startups was scored, considering that they are companies with great growth potential and, therefore, with great potential for contribution to Brazil, as they will generate income, jobs, revenue for the State, movement of the economy, among others. In addition, it was approached about the horizontality of the fundamental norms of the Brazilian legal system, mainly because the contracts, for the companies and even for the investments, have a commitment and commitment to the community, thus, it requires to attend the social function. Finally, it should be noted that the Brazilian legal system provides the entrepreneur with several options for corporate composition and organization of the company, thus, the choice of the type of company is extremely important for corporate protection, company management, attraction of investments and maintenance governance structure.